Development and validation of a method for the determination of the specific activity of recombinant monoclonal antibody eculizumab - D. I. Zybin; A. S. Seregin; A. D. Askretkov; N. V. Orlova; Yu. A. Seregin; A. I. Prostyakova; D. V. Kapustin (Тонкие химические технологии, 2020)
Objectives. Developing reliable and accurate analytical methods is necessary for comparative pharmaceutical analysis using physicochemical, biological (in vitro), preclinical, and clinical trials. The main objective of this study was to develop and validate an in vitro method for determining the specific activity of the recombinant monoclonal antibody eculizumab.Methods. The method of indirect enzyme immunoassay was used in the study.Results. A method for determining the specific activity of the humanized recombinant monoclonal antibody eculizumab was described and validated for the first time. A comparative evaluation of the specific activity of Soliris® (Alexion Pharmaceuticals Inc., USA), and its biosimilar PRK-001 (Pharmapark, Russia) was performed using the developed method.Conclusions. The similarity of PRK-001 and the original Soliris® in relation to their specific activity, that is, binding to the human complement system C5 protein, was proved.